Sakralisasi Negara: Praktik Ritual dan Konstruksi Sosial Ruang Publik di Jawa Kontemporer - Wibowo, Arif; Hasnawan, Dedi (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2026)
Religious rituals are not merely devotional practices but social processes through which meanings, identities, and spatial orders are produced and stabilized. This article examines the resilience of Sima'an al-Qur'an and Dhikr al-Ghafilin in Ponorogo, East Java, where large-scale gatherings persist amid urban modernity. Drawing on Peter L. Berger's sociology of knowledge, this qualitative study analyzes how ritual practices become durable social realities through externalization, objectivation, and internalization. Data were obtained through participant observation, in-depth interviews, and document analysis. The findings indicate that ritual participation reasserts moral order, institutionalizes collective meanings, and sacralizes bureaucratic public spaces, including state-associated venues. Internalization is reflected in participants' embodied piety and moral-emotional attachment. The study contributes to debates on public religion by demonstrating how ritual practices actively re-code public space and sustain sacred meanings within contemporary social contexts.